Maximum safety and minimum risk: midlineaccess gained by a nurse-led Vascular Accessand Infusion Team - Latos, Maciej; Zawadka, Mateusz; Kosson, Dariusz (Nursing in the 21st Century, 2023)
MAXIMUM SAFETY AND MINIMUM RISK: MIDLINE ACCESS GAINED BY A NURSE-LED VASCULAR ACCESS AND INFUSION TEAMAim. The aim of the study was to conduct a retrospective analysis of cannulations done under ultrasound guidance by the Vascular Access and Infusion Team using the Seldinger technique.Material and methods. This observational study was retrospective in nature. Analysis was carried out of 82 cannulation charts reporting procedures from March to August 2022 at the University Clinical Centre of the Medical University of Warsaw.Results. Midline access was gained in 86 patients with a success rate of 95.3% (n=82). Cannulation by nurses was performed in 93% (n=80) of the patients. The procedure required an average of 1.62 attempts. The most frequently cannulated veins were the basilic (72%, n=59) and brachial (14.6%, n=12) ones. MC removal in 40.2% (n=33) of the cases was due to the termination of intravenous therapy, and in 23.4% (n=19) was caused by complications related to infusion management.Conclusions. Implantation of midline catheters in patients, including those with difficult intravenous access, can be done effectively with a minimum number of cannulation attempts. Maintaining midline catheters for the entire duration of therapy is challenging due to potential complications and requires rigorous care during their use. A detailed analysis of possible complications distinguishing between different types of complications and continuous improvement of observation protocols and appropriate management is advisable. It is also advisable to plan and conduct an observational study in the area of retrospective analysis.